К изучению фауны мух семейства Sarcophagidae Каневского заповедника - Вервес, Ю.Г. (Вестник зоологии, 1973)
In Sarcophagidae fauna of the Kanev reservation 46 species of 3 subfamilies are Tegistered, 3 species are mentioned for the first time for the Ukraine. Steppe species with addition of taiga-forest and Mediterranean elements predominate. Some groups - coprobionts (dominating), necrobionts, predators and parasites are distinguished by trophic relations. Flight takes place from the end of April up to a half of October, flight apex - at the end of May beginning of June and August.